Lung tissue volume estimated by simultaneous radiographic and helium dilution methods. - Armstrong, J D (1982)
The pulmonary total tissue volume (blood, extravascular water, and dry tissue volume) was measured by finding the difference between the radiographic displacement volume of the thorax (RDVT) and the lung gas volume. Simultaneous determinations of RDVT and gas volume were made in 10 healthy subjects sitting upright. RDVT was determined from posteroanterior and lateral chest radiographs, a computerised modification of the Barnhard method being used; and gas volume was measured by helium dilution with each radiographic exposure. At functional residual capacity pulmonary total tissue volume was 843 +/- 110 ml (1 SD). The density of the lung (ml tissue per ml tissue and gas) was 0.19 +/- 0.03 (1 SD). This method, different in principle from indicator-dilution and acetylene rebreathing studies, provides measurements of total tissue volume.